High-performance computing applications in numerical simulation and edge computing : ACM ICS 2018 International Workshops, HPCMS and HiDEC, Beijing, China, June 12, 2018, Revised Selected Papers /: ACM ICS 2018 International Workshops, HPCMS and HiDEC, Beijing, China, June 12, 2018, Revised Selected Papers. (2019) - Unknown
No abstract available